Improving the Functions of the Election Supervisory Body Through Participatory Supervision - Mohamad Rhava Kavriandi Musa; Mohamad Rivaldi Moha (Universitas Negeri Gorontalo, 2022)
This study aims to determine enhancing the function of the election supervisory body through participatory supervision. The method used in this research is empirical research methodology and uses a qualitative approach as well as descriptive and qualitative analysis techniques. The results of this study indicate that increasing participatory supervision of the functions of the election supervisory body is carried out with two kinds of programs, the first is socialization which aims to build public awareness that they have an obligation to guard their right to vote in elections by participating in supervising the stages of the election administration. While the second is the corner of supervision can be interpreted as a center for the development of science and knowledge about democracy and election supervision.